The High Energy Density Scientific Instrument at the European XFEL. (23rd August 2021) - Zastrau, Ulf; Appel, Karen; Baehtz, Carsten; Baehr, Oliver; Batchelor, Lewis; Berghäuser, Andreas; Banjafar, Mohammadreza; Brambrink, Erik; Cerantola, Valerio; Cowan, Thomas E.; Damker, Horst; Dietrich, Steffen; et al.
Abstract : The unique parameters of the European XFEL enable novel and groundbreaking experiments in matter at extreme conditions at the High Energy Density (HED) scientific instrument. The performance of the HED instrument during its first two years of operation, its scientific remit, as well as ongoing installations towards full operation are presented. Abstract : The European XFEL delivers up to 27000 intense (>10 12 photons) pulses per second, of ultrashort (≤50 fs) and transversely coherent X‐ray radiation, at a maximum repetition rate of 4.5 MHz. Its unique X‐ray beam parameters enable groundbreaking experiments in matter at extreme conditions at the High Energy Density (HED) scientific instrument. The performance of the HED instrument during its first two years of operation, its scientific remit, as well as ongoing installations towards full operation are presented. Scientific goals of HED include the investigation of extreme states of matter created by intense laser pulses, diamond anvil cells, or pulsed magnets, and ultrafast X‐ray methods that allow their diagnosis using self‐amplified spontaneous emission between 5 and 25 keV, coupled with X‐ray monochromators and optional seeded beam operation. The HED instrument provides two target chambers, X‐ray spectrometers for emission and scattering, X‐ray detectors, and a timing tool to correct for residual timing jitter between laser and X‐ray pulses.